THE LAW AS A SOLUTION TO HEALTH PROBLEMS: LEGAL REMEDIES IN THE PRISON CONTEXT (Revista Paradigma, 2022)
The purpose of this article is to present mechanisms to compensate the health and physical integrity of prisoners due to the execution of the deprivation of liberty penalty as it is performed in Brazil. Given that the criminal justice system maintains, at the same time as producing, excesses and deviations in criminal enforcement, the present research sought to outline hypotheses of application of two procedural incidents provided for in the Penal Execution Law to combat or minimize, by way of the iniquities caused to the health of prisoners during confinement.